2018
DOI: 10.9734/jeai/2018/44045
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Biofertilizer Containing Growth-Promoting Bacteria on the Eggplant (Solanum melongena L.)

Abstract: The use of organic fertilisers in vegetable cultivation is important in the pursuit of increased production to improve the physical, chemical and biological characteristics of the soil, to promote plant growth, and to achieve economically viable productivity for farmers of small-and mediumsized farms. This study aimed to evaluate the development and productivity of eggplant after its fertilisation with a biofertiliser that was composed of sugar and alcohol waste and a bacteria growth promoter for plants. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The treatment likewise prompted expansion in plant level, stem distance across, leaf number, plant dry weight and leaf region. Jugnake et al [32] in Tamil Nadu found that the immunization of Azospirilium in blend with the nitrogenous manure expanded the yield up to 13.1% in Poovan [33]. The expanded bundle weight was likewise viewed as related with comparing expansion long of pack, number of hands, length, size and weight of fingers.…”
Section: Effect Of Biofertilizer On Growth Charactermentioning
confidence: 99%
“…The treatment likewise prompted expansion in plant level, stem distance across, leaf number, plant dry weight and leaf region. Jugnake et al [32] in Tamil Nadu found that the immunization of Azospirilium in blend with the nitrogenous manure expanded the yield up to 13.1% in Poovan [33]. The expanded bundle weight was likewise viewed as related with comparing expansion long of pack, number of hands, length, size and weight of fingers.…”
Section: Effect Of Biofertilizer On Growth Charactermentioning
confidence: 99%